2012
DOI: 10.1088/0957-4484/23/35/355304
|View full text |Cite
|
Sign up to set email alerts
|

A new approach causing the patterns fabricated by silver nanoparticles to be conductive without sintering

Abstract: Silver nanoparticles (Ag NPs) with a mean size of about 90 nm were synthesized by polyol reduction of silver nitrate with ethylene glycol (EG) in the presence of poly(vinyl pyrrolidone) (PVP). The Ag NPs undergo a spontaneous coalescence in the presence of chloride ions even without a traditional sintering process which occurs at a relatively high temperature. Such behavior can cause a rapid decrease in the resistivity of the patterns fabricated by Ag NPs. Conductive silver lines were successfully fabricated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 35 publications
(37 reference statements)
3
51
0
Order By: Relevance
“…4a. The nanoparticles also have a wide size distribution, which could be attributed to Ostwald ripening [3,9,16]. The presence of large particles suggests that sintering and growth possibly occurred.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…4a. The nanoparticles also have a wide size distribution, which could be attributed to Ostwald ripening [3,9,16]. The presence of large particles suggests that sintering and growth possibly occurred.…”
Section: Methodsmentioning
confidence: 99%
“…1a. It has been reported that Cl -ions can cause the detachment of capping gents, such as PVP that surround the nanoparticles [3,9,16]. Due to high affinity of Ag with Cl -ions, PVP molecures are possibly desorbed from the surface of the nanoparticles.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations